Selected Abstracts of the 9th International Workshop on Neonatology; Cagliari (Italy); October 23-26, 2013 - - (Hygeia Press di Corridori Marinella, 2013)
Selected Abstracts of the 9th International Workshop on Neonatology • LEARNED LESSONS, CHANGING PRACTICE AND CUTTING-EDGE RESEARCH • Cagliari (Italy) • October 23rd-26th 2013 The Workshop has been organized on behalf of Union of European Neonatal and Perinatal Societies, Union of Mediterranean Neonatal Societies, Italian Society of Neonatology, UNICEF, and under the High Patronage of the President of the Italian Republic.   ABS 1. Aetiology and type of reference hospital for neonatal transport in Greece during 2012 • S. Mouskou, C. Varakis, D. Pyrros, N. Iacovidou; Athens (Greece) ABS 2. Changes in neonatal outcomes of very low birth weight infants in Hospital of Lithuanian University of Health Sciences • K. Stuikiene, R. Tameliene, D. Stoniene, A. Kudreviciene, V. Ivanauskiene; Kaunas (Lithuania) ABS 3. Autoimmune liver disease in childhood • Y. Gibo, D. Fanni, P. Van Eyken, S. Nemolato, G. Floris, C. Gerosa; Matsumoto (Japan), Leuven (Belgium) and Cagliari (Italy) ABS 4. Lactoferrin attenuates intestinal injury afther perinatal hypoxia and hypothermia • N. Barisic, G. Konstantinidis, V. Stojanovic, A. Doronjski, S. Spasojevic; Novi Sad (Serbia) ABS 5. Osteopenia in prematurity: case report • K. Stuikiene, R. Tameliene, D. Stoniene, A. Kudreviciene, V. Ivanauskiene; Kaunas (Lithuania) ABS 6. Neonatal Bartter syndrome: case report of a very unusual entity • A. Koutroumpa, K. Georgiou, H. Georgaki, F. Anatolitou; Athens (Greece) ABS 7. Placental Growth Factor (PlGF) and placental function • I. Atzeni, S.F. Deiana, A. Meloni, B. Piras, P. Zedda, S. Soddu, G. Parodo, G. Faa, G.B. Melis, A.M. Paoletti; Cagliari (Italy) ABS 8. Neonatal ECMO: initial experience of Hospital de São João • G. Rocha, P. Soares, T. Henriques-Coelho, J. Correia-Pinto, J. Monteiro, H. Guimarães, R. Roncon-Albuquerque Jr; Porto (Portugal) ABS 9. GCMS-based metabolomics analysis of urines in hypoxic neonatal piglets • C. Fattuoni, L. Barberini, N. Iacovidou, T. Xanthos, A. Papalois, E. d'Aloja, G. Finco, A. Noto, A. Dessì, V. Fanos; Cagliari (Italy) and Athens (Greece) ABS 10. Combined oral Sildenafil and Bosentan in a ex-preterm infant with bronchopulmonary dysplasia, sepsis and severe pulmonary arterial hypertension refractory to inhaled nitric oxide • E. Gitto, L. Marseglia, S. Aversa, M.P. Calabrò, I. Barberi; Messina (Italy) ABS 11. The importance of the National Academy of Sciences, Letters and Arts of Modena for the history of Pediatrics • I. Farnetani, F. Farnetani; Milan, Modena and Reggio Emilia (Italy) ABS 12. Alternative use of paracetamol in PDA closure: three case reports • C. Fanni, R. Irmesi, M. Testa, M.A. Marcialis, M.C. Pintus, F. Cioglia, S. Puddu, C. Loddo, V. Fanos; Cagliari (Italy) ABS 13. Males in Sardinia are the healthiest of Italy • I. Farnetani, F. Farnetani; Milan, Modena and Reggio Emilia (Italy) ABS 14. Renal pelvis perforation: a rare complication of long line in a premature infant • L. Marseglia, S. Manti, G. D'Angelo, E. Gitto, G. Quartarone, I. Barberi; Messina (Italy) ABS 15. The chair of childcare in Florence was established by the Sovereign Military Order of Malta • I. Farnetani, M.C. Gallorini Farnetani, F. Farnetani; Milan, Arezzo, Modena and Reggio Emilia (Italy) ABS 16. Nurse Led Clinic: wellbeing for mother and son • C. Ennas, A. Dessì, A. Fenu, E. Pilloni, D. Pireddu, M. Crisafulli, V. Fanos; Cagliari (Italy) ABS 17. Emotional states of mothers of premature babies three months after discharge • P. Paladini, A. Frisenna, L. Valletta, A. Paladini; Lecce and Rome (Italy) ABS 18. Recurrent benign pneumoperitoneum in a moderately preterm newborn infant • F. Zaglia, F. Doro, S. Spaggiari, A. Coghi, L. Lubrano, E. Andreatta, P. Biban; Verona (Italy) ABS 19. Dosimetric issues in a Neonatal Intensive Care Unit • A. Bernardini, V. Fanti, L. Satta, M. Puddu, V. Fanos; Cagliari (Italy) ABS 20. Self-healing Langerhans cell histio-cytosis (Hashimoto-Pritzker disease) in a 5-month-old child • P. Bianco, B. Piras, G. Senes, L. Pilloni; Cagliari (Italy) ABS 21. Recurrent preterm delivery and histological chorioamnionitis: a case report • S. Soddu, A. Meloni, F. Delfino, M. Puddu, M. Pautasso, S.F. Deiana, M. Testa, I. Murgianu, G. Parodo; Cagliari (Italy) ABS 22. Bcl-2 immunoreactivity in the newborn kidney: a new marker for cap mesenchymal cells • E. Obinu, D. Fanni, C. Gerosa, E. Di Felice, S. Nemolato, A. Dessì, V. Marinelli, L. Ruggeri, B. Pinna, G. Faa, V. Fanos, R. Ambu; Cagliari (Italy) ABS 23. Relevant changes in nephrogenesis in Down syndrome • G. Parodo, S. Soddu, A. Crobe, M. Desogus, A.M. Paoletti, G. Ottonello, V. Zurrida, D. Gariel, G. Secci, L. Cataldi; Cagliari and Rome (Italy) ABS 24. Interindividual variability in Langerhans islet burden in newborn pancreas at birth • G. Locci, A. Pinna, S. Nemolato, V. Mais, C. Gerosa, D. Fanni, C. Loddo, M. Testa, I. Murgianu, A.M. Nurchi; Cagliari (Italy) ABS 25. G6PD deficiency in Sardinian newborn: the utility of molecular test • R. Carboni, A. Dessì, M.C. Sollaino, G. Ottonello, L. Costa, E. Vannelli, L. Beltrano, M.B. Botta, D. Susto, P. Moi; Cagliari (Italy) ABS 26. Morphogenesis and molecular mechanisms involved in human exocrine and endocrine pancreas development • A. Pinna, G. Locci, S. Nemolato, C. Gerosa, C. Fanni, A.M. Nurchi, M.A. Marcialis, M.C. Pintus, A. Dessì, R. Ambu; Cagliari (Italy) ABS 27. Massive myocardial infarction in a newborn with Idiopathic Infantile Arterial Calcification • R. Ambu, A. Faa, C. Gerosa, D. Fanni, V. Marinelli, F. Birocchi, F. Cioglia, G. Palmas, P. Neroni, P.P. Bassareo; Cagliari (Italy) ABS 28. Vitamin D status and type of feeding in a group of 50 unsupplemented infants (1 month - 2 years) • M. Fanos, F. Vierucci, M. Gori, F. Simi, P. Erba, G. Saggese; Pisa (Italy) ABS 29. Multidisciplinary care to achieve humanization in pregnancy at high risk of preterm birth • I. Melis, M. Zonza, M. Puddu, B. Vacca, K. Martsidis, P. Zedda, R. Mura, S. Soddu, A.M. Paoletti, G.B. Melis, A. Meloni; Cagliari (Italy) ABS 30. An unexpected case of GBS early-onset meningo-sepsis • D. Olla, A.R. Denotti, E. Coni, G. Ottonello; Cagliari (Italy) ABS 31. Relevant hystological alterations in neonatal kidney: 5 case reports • C. Loddo, M. Puddu, S. Puddu, C. Gerosa, D. Fanni, C. Fanni, G. Ottonello, E. Trudu, P. Van Eyken, V. Fanos, G. Faa; Cagliari (Italy) and Leuven (Belgium) ABS 32. Variability in drug use among newborns admitted to NICUs: a proposal for an European multicentre study • L. Cuzzolin; Verona (Italy) ABS 33. Gastrointestinal disorders in the newborn: proposal of a practical flow-chart • A. De Magistris, M.A. Marcialis, M.C. Pintus, A. Reali, S. Puddu, V. Fanos; Cagliari (Italy) ABS 34. Sudden infant death syndrome and the right sleep position: an irrational information strategy on a very serious issue • S. Mouskou, C. Varakis, E. Ioannidou, P. Troizos-Papavasileiou, N. Varakis, N. Iacovidou; Athens and Rethymno (Greece) ABS 35. Attenuation measurements of infant incubators in radiological practice • A. Bernardini, V. Del Rio, V. Fanti, L. Satta, E. Tumminia, M. Puddu, V. Fanos; Cagliari (Italy) ABS 36. In vitro kidney embryonic cell proliferation during indomethacin and ibuprofen administration • G. Pichiri, E. Di Felice, A. Sanna, A. Dessì, M. Puddu, E. Puxeddu, G. Faa, V. Fanos, P.P. Coni; Cagliari (Italy) ABS 37. Congenital syphilis in Brazil: A preventive challenge • M. Valverde Pagani, R. Leandro de Souza; Rio de Janeiro (Brazil) ABS 38. Relationship between Infections and the invasive procedure in VLBW premature: the role of the nurse • G. Cruccu, P. Casula; Cagliari (Italy) ABS 39. Right sided pulmonary agenesis • C. Fanni, M.A. Marcialis, M.C. Pintus, M. Testa, A. De Magistris, C. Loddo, R. Irmesi, E. Coni, G. Secci, S. Puddu, M. Puddu; Cagliari (Italy) ABS 40. Enteral nutrition in preterm infants: current practical issues for the daily practice • R. Örs; Konya (Turkey) ABS 41. Erythropoietin adiministration effetcs on heart in Landrace/Large White pigs exposed to ventricular fibrillation • A. Faa, V. Fanos, N. Iacovidou, E. Di Felice, P. Pampaloni, D. Fanni, D. Scano, C. Gerosa, M.E. Pais, T. Xanthos; Cagliari (Italy) and Athens (Greece) ABS 42. A case of Necrotizing Enterocolitis (NEC) in a full-term newborn • E. Coni, R. Irmesi, D. Olla, L. Mascia, M.A. Marcialis, M. Corsello, A. De Magistris, S. Puddu, G. Ottonello, P.